The Tale of the Tulsi Plant and Other Studies - Kincaid, C.A., (Brill | Manohar Publishers & Distributors, 2024)
This book focuses on Western India. The book begins with the story of Tulsi (Basil) plant, Shami (Ghaf) and Indian Bel (Bael) tree. It covers the history of the Maratha Empire, the arrival of Mughals in Deccan during the period of Aurangzeb, the emergence of the Maratha confederacy under the Peshwa rule, and the emergence and the subsequent rule of British East India Company. This book covers the interactions of Portuguese subjects with the Marathas, the bakhar literature of Dabhades and Gaikwads, and the court scenes. Also, this book contains sayings and philosophies from Kathiawar, Deccan, and compositions by Muslim and Parsee communities.